The role of watershed management in addressing socioeconomic challenges of rural households in the upper Gelana watershed of Ethiopia - Tsedey Tesfahun; Assefa Abegaz; Esubalew Abate Alemu (Discover Sustainability)
Abstract The study aimed to examine how watershed management assists in addressing the socioeconomic challenges faced by smallholders in the Upper Gelana watershed. A total of 150 rural family heads contributed field data for this study between January and March 2023. The sample size selection was determined using the Yamane random sampling formula. A comprehensive household-level survey and key informant interviews were utilized to collect the data. The data were analyzed using SPSS software, version 24. The analysis employed multinomial regression and descriptive statistics. A grading scale ranging from 0 to 1 was used to assess the five livelihood assets: human, financial, physical, natural, and social capital. Among these, social capital received the lowest score (0.47), whereas financial capital achieved the highest score (0.86). Furthermore, the results of the multinomial logistic regression analysis indicated that household behavior in the implementation of watershed management measures was significantly influenced by education, the availability of loans, and access to extension services. The results of the study indicated that while watershed management techniques enhanced income, food security, and access to essential services, a significant portion of respondents continued to experience financial difficulties and remained engaged in subsistence farming. Consequently, both immediate and long-term efforts are necessary to recover from a prolonged socioeconomic challenges, alongside watershed management practices. To effectively address the socioeconomic needs of rural households and foster future resilience, the study recommends policy initiatives aimed at improving access to extension services, credit, and information on effective strategies.